2016
DOI: 10.1002/ecs2.1465
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is advancing spring onset across the U.S. national park system

Abstract: Abstract. Many U.S. national parks are already at the extreme warm end of their historical temperature distributions. With rapidly warming conditions, park resource management will be enhanced by information on seasonality of climate that supports adjustments in the timing of activities such as treating invasive species, operating visitor facilities, and scheduling climate-related events (e.g., flower festivals and fall leaf-viewing). Seasonal changes in vegetation, such as pollen, seed, and fruit production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 64 publications
6
47
0
Order By: Relevance
“…A new paradigm for protected-area conservation has emerged that recognizes the highly dynamic and vulnerable nature of park ecosystems and emphasizes active interventions (e.g., restoration; Hobbs et al 2010). Monahan et al (2016) show us that the onset of spring is advancing in most parks, as Monahan and Fisichelli (2014) have demonstrated previously that the entire NPS system is actively experiencing temperature increases. This is particularly evident in the papers about global change impacts on parks.…”
Section: Special Feature Highlightssupporting
confidence: 60%
“…A new paradigm for protected-area conservation has emerged that recognizes the highly dynamic and vulnerable nature of park ecosystems and emphasizes active interventions (e.g., restoration; Hobbs et al 2010). Monahan et al (2016) show us that the onset of spring is advancing in most parks, as Monahan and Fisichelli (2014) have demonstrated previously that the entire NPS system is actively experiencing temperature increases. This is particularly evident in the papers about global change impacts on parks.…”
Section: Special Feature Highlightssupporting
confidence: 60%
“…Using statistical and modeling approaches, researchers have been able to assess the impact of changing temperature on flowering onset, as well as address other questions using these data sets (Appendix S1: Table B). To develop a statistical approach to assess the relative phenology changes in 276 U.S. National Parks and Preserves across the contiguous United States and Alaska, Monahan et al (2016) used species-specific spring indices for three nonnative indicator species (a cloned lilac cultivar and two honeysuckle species commonly found in these locations). Spring indices included first leaf and first bloom indices, which are based on the number of accumulated growing degree-days.…”
Section: Plant-focused Studiesmentioning
confidence: 99%
“…Other studies have likewise reported that earlier springs drove trends in reduced winter duration (Dye 2002, Allen and Sheridan 2016, Kutta and Hubbart 2016. In addition, proxies for the beginning of spring, particularly phenological data describing budbreak, leaf emergence, and leaf out, have been widely used to document earlier springs (Richardson et al 2006, Schwartz et al 2013, Piao et al 2015, providing further evidence for an advancement of spring onset by −0.8 to −0.9 d per decade in the northeastern US from 1901 to 2012 (Monahan et al 2016). Our findings of later onset of winter, earlier onset of spring, and the overall shortening of the winter period resonate with the results of previous investigations of shifting vegetation phenology.…”
Section: Discussionmentioning
confidence: 99%